Minimum protection in DC funding pension plans and Margrabe options - Pierre Devolder; Sébastien de Valeriola (Risks, 2017)
The regulation on the Belgian occupational pension schemes has been recently changed. The new law allows for employers to choose between two different types of guarantees to offer to their affiliates. In this paper, we address the question arising naturally: which of the two guarantees is the best one? In order to answer that question, we set up a stochastic model and use financial pricing tools to compare the methods. More specifically, we link the pension liabilities to a portfolio of financial assets and compute the price of exchange options through the Margrabe formula.
Keywords: 330; pensions; Defined Contributions; guaranteed rate; option theory; Margrabe formula